2017
DOI: 10.1186/s13071-017-2530-9
|View full text |Cite
|
Sign up to set email alerts
|

Variations in visceral leishmaniasis burden, mortality and the pathway to care within Bihar, India

Abstract: BackgroundVisceral leishmaniasis (VL) has been targeted by the WHO for elimination as a public health problem (< 1 case/10,000 people/year) in the Indian sub-continent (ISC) by 2020. Bihar State in India, which accounts for the majority of cases in the ISC, remains a major target for this elimination effort. However, there is considerable spatial, temporal and sub-population variation in occurrence of the disease and the pathway to care, which is largely unexplored and a threat to achieving the target.MethodsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…The finding of this study revealed that males VL patients accounted a larger (93.2%) proportion compared to female VL patients (6.8%). This result also supported by Sarah, et al [7]; Perry, et al [8].…”
Section: Discussionsupporting
confidence: 80%
“…The finding of this study revealed that males VL patients accounted a larger (93.2%) proportion compared to female VL patients (6.8%). This result also supported by Sarah, et al [7]; Perry, et al [8].…”
Section: Discussionsupporting
confidence: 80%
“…This is the experience of the Guinea-worm and poliomyelitis campaigns [19], as well as the context behind Dowdle and Cochi's summation that "all eradication is ultimately local" [20] (p. 3). The central importance attached to diagnosis, as a means by which one might hope to understand and manage local settings, is now a key message coming out of the literature [21][22][23]. In this view, diagnostics and the data they yield promise to become a missing piece in the puzzle of disease elimination.…”
Section: Ntds and Disease Eliminationmentioning
confidence: 99%
“…There are two model variants, that only differ based on assumptions about where the main reservoir of infection lies; namely, solely in symptomatic individuals (VL and PKDL), or mainly in asymptomatic individuals [21,35,36]. The models were parameterized with age-structured data on approximately 21,000 individuals included in the KalaNet bednet trial in India and Nepal [37] and have undergone geographical cross-validation against data on >5000 VL cases from 8 endemic districts in Bihar collected by CARE India [38] (see [36] In the alternative model variant, asymptomatic individuals are assumed not to be infectious towards to sand fly, with infection pressure only coming from symptomatic individuals with VL (with and without treatment) and PKDL. Once a susceptible individual is infected by an infectious sand fly, they become early asymptomatic for an average duration of about 200 days, which is followed by the late asymptomatic stage (average duration of 69 days).…”
Section: Transmission Models and Simulation Of Existing Interventionsmentioning
confidence: 99%